Effects of off-pump versus on-pump coronary artery bypass grafting on early and late right ventricular function. - Pegg, T; Selvanayagam, J; Karamitsos, T; Arnold, R; Francis, J; Neubauer, S; Taggart, D (2008)
BACKGROUND: Off-pump CABG (OPCABG) results in better preservation of left ventricular function in the perioperative period than conventional on-pump CABG (ONCABG); however, evidence is conflicting as to the effect of OPCABG and ONCABG on right ventricular (RV) function, possibly because of the complexity involved in measuring this. METHODS AND RESULTS: In a single-center randomized pilot study, 60 patients with normal left ventricular function undergoing CABG were randomly assigned to OPCABG or ONCABG. Patients underwent cardiac magnetic resonance imagine for assessment of RV function preoperatively, early postoperatively, and at 6 months after surgery. Fifty-one patients completed the first 2 scans, and 47 completed all 3 scans. Preoperative characteristics and RV function did not differ significantly between the 2 groups (mean+/-SD): RV stroke volume index was 49+/-10 mL/m(2) for OPCABG and 49+/-16 mL/m(2) for ONCABG. After surgery, RV stroke volume index fell to 36+/-7 mL/m(2) in the OPCABG group and 39+/-11 mL/m(2) in the ONCABG group, but this did not differ significantly between the 2 groups (P=0.41). All markers of RV function recovered to preoperative levels by 6 months, with no long-term difference between the surgical techniques. CONCLUSIONS: RV function is impaired early after surgery but recovers by 6 months. The changes were similar in both the OPCABG and ONCABG groups.